A TRANSLATION ANALYSIS ON IDIOMATIC EXPRESSIONS IN “THE INTERNSHIP” MOVIE BASED ON LARSON’S THEORY (SUBTITLED BY JACK AND THE WILEE) - Lidya Fina Syafitri (Universitas Bengkulu, 2018)
This research is aimed at analyzing the idiomatic expressions encountered in “The Internship” movie subtitled by Jack and The Wilee. This movie was translated as ideal translation based on Larson’s theory and to explain how the idiomatic expressions translation of “The Internship” movie are acceptable or not based on Larson’s theory. The object of this study is “The Internship” Movie Subtitle by Jack and the Wilee. In this research, the researcher collected the data by using documentation (library research). Then, there were several steps in procedure of data analysis which was known as Preparing and organizing the data, Coding, and the last steps is Re-presenting the data. According to Larson’s table that the researcher used to analyze the translation appropriateness with Larson’s Criteria of Ideal Translation, the researcher gets the result that show the translation of idiomatic expressions are acceptable or not with Larson’s Criteria. There are three criteria of ideal translation based on Larson’s Theory named Accurate (A), Clear (C), and Natural (N). From the total 55 Idiomatic Expression the researcher shows 80% are Ideal-acceptable translation (I-Acc), 11% are Acceptable translation (Acc), 2% are Unacceptable translation (Un-Acc), and 7% are Failed translation (F). Overall, the translation of idiomatic expression by Jackandthewilee is Acceptable